The Relationship between the Internal Labour Market and Transitions from Temporary to Permanent Employment in Korea - Kim, Hyondong; Lee, Dong-Jin (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
SummaryOver the past decade, Korean businesses have experienced significant growth in the proportion of temporary employment. In response, the Korean government has enacted the “Temporary Employment Protection Act” to curb the use of temporary employment. With these legislative changes, Korean employers confront choices about whether to encourage transitions from temporary to permanent employment or to utilise outsourcing/contracting services. The purpose of this study is to explore internal labour markets (ILMs) and investigate why companies are willing to transform temporary employment into permanent employment. Furthermore, in the face of market volatility, we consider how companies are willing to increase the number of temporary workers in order to more easily adjust the numbers and types of human resources, rather than constructing and establishing ILMs within a firm. By investigating the interrelated relationships between ILMs, environmental dynamism, and transitions from temporary to permanent employment status, this study elaborates the features of ILMs in making employment decisions. The statistical results of this study show that structural elements of ILMs facilitate transitions from temporary to permanent employment. Among ILMs, only seniority-based pay plans reduce the number of permanent employees transferred from temporary status when companies experience dynamic changes in their environments. Furthermore, ILMs exerted greater influences over employers’ decisions about transitions from temporary to permanent employment a few years after the enactment of changes in temporary labour laws and regulations. This study shows that the features of an employment system determine companies’ decisions about temporary versus permanent employment. ILMs shape and establish organisational norms and cultural traditions that determine employment structures. Furthermore, institutionalised environments also determine whether employers decide to make transitions from temporary to permanent employment. Future studies should pay attention to the features of employment systems as determinants regarding firms’ human capital.